2002
DOI: 10.1103/physrevlett.88.250402
|View full text |Cite
|
Sign up to set email alerts
|

Transverse Breathing Mode of an Elongated Bose-Einstein Condensate

Abstract: We study experimentally the transverse monopole mode of an elongated rubidium condensate. Because of the scaling invariance of the nonlinear Schrödinger (Gross-Pitaevskii) equation, the oscillation is monochromatic and sinusoidal at short times, even under strong excitation. For ultralow temperatures, the quality factor Q = omega(0)/gamma(0) can exceed 2000, where omega(0) and gamma(0) are the mode angular frequency and damping rate. This value is much larger than any previously reported for other eigenmodes o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

20
175
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(197 citation statements)
references
References 35 publications
20
175
2
Order By: Relevance
“…5. There is an additional frequency shift due to nonzero temperature [4][5][6][7] which is estimated to be negligible given our low temperatures and interaction strength [43]. Even though we can neglect temperature effects in the measurements presented here, our method of excitation of the quadrupole mode may be used to study these effects in further detail in regimes of stronger interactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5. There is an additional frequency shift due to nonzero temperature [4][5][6][7] which is estimated to be negligible given our low temperatures and interaction strength [43]. Even though we can neglect temperature effects in the measurements presented here, our method of excitation of the quadrupole mode may be used to study these effects in further detail in regimes of stronger interactions.…”
mentioning
confidence: 99%
“…Collective excitation of a Bose-Einstein condensate (BEC) is an essential diagnostic tool for investigating properties of the ultracold quantum state. Fundamental information about condensate dynamics can be determined from observations of collective modes [1][2][3], including the effects of temperature [4][5][6], and the dimensionality of the system [7]. In addition, the interplay between these modes and external agents, such as random potentials [8,9], lattices [10,11], as well as other atoms [12][13][14][15][16], can be investigated.…”
mentioning
confidence: 99%
“…The observations of low-lying excitations [1,2,3], including the scissor mode [4], were an important step toward the characterization of these systems. Collective excitations were also studied at finite temperature [5,6,7,8] investigating frequency shifts and damping rates. All the experiments so far reported were performed on Bose-Einstein condensates magnetically trapped in pure harmonic potentials.…”
mentioning
confidence: 99%
“…In this regard, the results in [37] are also of interest, where propagation and absorption of the transverse breathing mode of an elongated BEC were investigated experimentally in 87 Rb vapour. The authors of the mentioned study, attempting to measure the damping rate of these modes at the temperature approximately equal to 40 ÷ 60 nK, had found that the behaviour of the perturbation amplitude in this temperature region differs significantly from the behaviour of the amplitude of a damped sinusoidal signal.…”
Section: Resultsmentioning
confidence: 99%
“…We also would like to draw attention to the fact that temperature range 40 ÷ 60 nK corresponds to the values of quantity a in terms of the present paper that are in the 0.7 ÷ 1.0 range. The value of a is naturally calculated according to formula (4.9) and using the values of the physical characteristics of the system [37]. In other words, in the mentioned case [37], it deals with the nearest neighbourhood of the point a ≈ 0.847 where the nonanalytic dependence of the dispersion characteristics on temperature is revealed.…”
Section: Resultsmentioning
confidence: 99%